Eosinophils, but Not Type 2 Innate Lymphoid Cells, Are the Predominant Source of Interleukin 4 during the Innate Phase of Leishmania major Infection - Sasse, Carolin; Barinberg, David; Obermeyer, Stephanie; Debus, Andrea; Schleicher, Ulrike; Bogdan, Christian (Pathogens, 2022)
Interleukin (IL)-4 plays a central role in the initiation of a type 2 T helper cell (Th2) response, which leads to non-healing and progressive infections with the protozoan parasite Leishmania (L.) major. Here, we tested the hypothesis that type 2 innate lymphoid cells (ILC2), which promote the development of Th2 cells, form an important source of IL-4 early after intradermal or subcutaneous L. major infection. Lineage-marker negative CD90.2(+)CD127(+)PD1(-) ILC2 were readily detectable in the ear or foot skin, but hardly in the draining lymph nodes of both naive and L. major-infected self-healing C57BL/6 and non-healing BALB/c mice and made up approximately 20% to 30% of all CD45(+)SiglecF(-) cells. Dermal ILC2 of C57BL/6 mice expressed the inducible T cell-costimulator (ICOS, CD278), whereas BALB/C ILC2 were positive for the stem cell antigen (Sca)-1. Within the first 5 days of infection, the absolute numbers of ILC2 did not significantly change in the dermis, which is in line with the unaltered expression of cytokines activating (IL-18, IL-25, IL-33, TSLP) or inhibiting ILC2 (IL-27, IFN-gamma). At day 5 to 6 post infection, we observed an upregulation of IL-4, but not of IL-5, IL-10 or IL-13 mRNA. Using IL-4-reporter (4get) mice, we found that the production of IL-4 by C57BL/6 or BALB/c mice was largely restricted to CD45(+)FSiglecF(+) cells of high granularity, i.e., eosinophils. From these data, we conclude that eosinophils, but not ILC2, are a major innate source of IL-4 at the skin site of L. major infection.
CRIS-Team WoS Importer:2022-09-09

The immunomicrotope of Leishmania control and persistence - Bogdan, Christian; islam, Noor-A-kasida; Barinberg, David; Soulat, Didier; Schleicher, Ulrike; Rai, Baplu (Trends in Parasitology, 2024)
Leishmania is an intracellular protozoan transmitted by sand fly vectors; it causes cutaneous, mucocutaneous, or visceral disease. Its growth and survival are impeded by type 1 T helper cell responses, which entail interferon (IFN)-γ-mediated macrophage activation. Leishmania partially escapes this host defense by triggering immune cell and cytokine responses that favor parasite replication rather than killing. Novel methods for in situ analyses have revealed that the pathways of immune control and microbial evasion are strongly influenced by the tissue context, the micro milieu factors, and the metabolism at the site of infection, which we collectively term the ‘immunomicrotope’. Understanding the components and the impact of the immunomicrotope will enable the development of novel strategies for the treatment of chronic leishmaniasis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: evasion; immunity; Leishmania parasites; leishmaniasis; micro milieu factors; persistence